Utilização sistêmica de estrôncio não radioativo como potencializador da osseointegração de implantes: avaliação biomeânica, microtomográfica e histomorfométrica em ratos - Scardueli, Cássio Rocha [UNESP] (2014)
Drugs containing bisphosphonates have been widely used to treat diseases such as osteoporosis, multiple myeloma, myeloproliferative disease and cancer with bone metastases. However, can not be used routinely in dental practice in favor of greater bone repair and osseointegration due to its specific mechanisms and are constantly related issues such as high permanence of the drug in the body and risk of bone necrosis. Drugs based on strontium emerge as new forms of treatment for osteoporotic patients as well as a possible indication for adjuvant use in surgical procedures, promoting new bone formation. Given the advantages offered by drugs containing strontium as strontium ranelate and strontium chloride/strontium carbonate , this study aimed to evaluate the osseointegration of implants in rat tibia. Were used 70 rats Rattus Norvegicus, males, randomly divided into 5 groups: S (control-serum physiologic); RE50 (Strontium Ranelate 50 mg); RE 625 (Strontium Ranelate 625 mg); ClE/CaE 30 (Strontium Carbonate and Strontium Chloride 30 mg); ClE/CaE 365 (Strontium Carbonate and Chloride Strontium 365 mg). The drugs were administered daily by gavage according to each group, starting 15 days before surgery (1 implant in each tibia) and persisted until the end of the experiment 15 or 60 days. Biomechanical tests were performed with the right implants through shift against removal, and implants in the left side microtomography and histomorphometric analysis were performed. The results showed an improvement in osseointegration, especially in groups strontium ranelate 625mg and strontium cloride/strontium carbonate 365mg in microtomography and biomechanical testing. The drug strontium base had a positive influence on osseointegration of implants, especially strontium chloride/strontium carbonate, can be incorporated into prevention, treatments of pathologies and surgical procedures as adjunct to implant placement.